1997
DOI: 10.1097/00003246-199706000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic outcome of patients undergoing tracheostomy for prolonged mechanical ventilation in New York state during 1993

Abstract: Care of patients who undergo tracheostomy for prolonged mechanical ventilation is expensive. The older the patient, the less satisfactory the outcome from an economic, clinical, and possibly social perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 12 publications
3
29
0
3
Order By: Relevance
“…This percentage is compatible with those of other reports in the literature 1,14,15 . The causes of failure to wean from mechanical ventilation in these patients related mainly to the presence of cardiac dysfunction and prolonged time of extracorporeal circulation.…”
Section: Discussionsupporting
confidence: 93%
“…This percentage is compatible with those of other reports in the literature 1,14,15 . The causes of failure to wean from mechanical ventilation in these patients related mainly to the presence of cardiac dysfunction and prolonged time of extracorporeal circulation.…”
Section: Discussionsupporting
confidence: 93%
“…Although specific epidemiological data do not exist, one study showed that this population represents ,10% of ICU admissions and consumes a significant amount of the overall ICU patient-days and ,50% of financial resources [154]. Two other studies demonstrated that up to 20% of medical ICU patients remained dependent on ventilatory support after 21 days [155,156].…”
Section: Question 5: How Should Patients With Prolonged Weaning Failumentioning
confidence: 99%
“…Proposed advantages for tracheostomy include easier airway management, improved patient comfort and communication, reduction in sedative use, earlier weaning from respiratory support, improved respiratory mechanics, earlier transition to oral feeding, reduced oropharyngeal trauma and prevention of ventilator-acquired pneumonia [156,160]. Adverse effects include misplacement, haemorrhage, obstruction, displacement, impairment of swallowing reflexes and late tracheal stenosis.…”
Section: Question 5: How Should Patients With Prolonged Weaning Failumentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mechanical ventilation in elderly patients is increasing [26,27], and age may play a factor in mortality and morbidity for those with respiratory conditions that require mechanical ventilation [26,[28][29][30][31][32][33]. Mortality rates after respiratory failure are higher with increasing age although other factors such as premorbid health status also impact prognosis.…”
mentioning
confidence: 99%